Patients and informal caregivers in the lead: a qualitative study on the experiences of patients, informal caregivers, and healthcare professionals with involvement in treatment, e-health and self-management programs - Matthijs H. Bosveld; Anne G.M. Smits; Helena J.M.M. Mertens; Michel J.J.M. van Zandvoort; Walther N.K.A. van Mook; Marloes A. van Bokhoven (BMC, 2024)
Abstract Background A significant proportion of patients and informal caregivers favor an active role in decisions concerning their health. Simultaneously, governments aim to shift treatment from a professional care setting to a community setting, in light of an ageing population, a decreasing number of health workers and allocation of scarce resources. This transition of care solicits patients' and informal caregivers' ability to self-manage. Therefore, the Maastricht University Medical Centre + has established the Academy for Patients and Informal caregivers. The aim is to proactively and professionally support patients and their informal caregivers to enhance their self-management. For that, the Academy offers activities in three categories: (1) instruction of nursing techniques, (2) training of e-health competencies and (3) the provision of self-management programs. Both patients with an episodic care need, as well as patients and informal caregivers with chronic illness, are eligible to participate in the Academy's activities. However, little is known about the experience of these interventions from the perspective of patients, informal caregivers and healthcare professionals. Methods We conducted semi-structured interviews with 15 patients, 8 informal caregivers and 19 health care professionals who either participated in, referred to or received patients from the Academy. Topics revolved around self-management and the Quadruple aim, covering topics such as patient experiences, healthcare costs, health and well-being of the population and improving work life for health professionals. Data were analyzed using thematic analysis. Results Patients and caregivers experienced an increase in the ability to manage health needs independently, leading to increased mental well-being and self-efficacy. They felt recognized as partners in care, although managing illness needs came with its own burdens. Health care professionals indicated that they felt assured of the quality, uniformity and availability of activities due to its central organization, with instruction nurses finding greater meaning in their work. On the level of health care systems, participants in this study mentioned a decrease in use of formal healthcare, whilst enabling a more equitable division of care. Conclusion Stakeholders' experiences with the Academy for Patients and Informal caregivers indicate that participation contributes to development of self-management, whilst also improving working conditions, reducing the appeal to formal care and advancing equity in healthcare. The burden for patients and informal caregivers is to be considered in future developments.